Radiation damage in uranium target of the accelerator driven system “KIPT Neutron Source” - Gann, V.V.; Gann, A.V.; Borts, B.V.; Karnaukhov, I.M.; Parkhomenko, A.A. (Вопросы атомной науки и техники, 2021)
In this work, the rate of radiation damage production in a uranium target of the neutron source at NSC KIPT under electrons irradiation with an energy of 100 MeV was estimated. The contribution of elastic and inelastic processes is determined: high-energy electrons and gamma quanta, photo-neutron production, fragments arising from photo-fission, damage from neutrons. It was found that the main input into damage production in a uranium target give fragments of photo-fission. Проведено розрахунки швидкості утворення зміщень в урановій мішені джерела нейтронів ННЦ ХФТІ під впливом опромінення високоенергетичними електронами з енергією 100 МеВ. Визначено внесок пружних та непружних процесів: високоенергетичних електронів та гамма-квантів, фотонейтронів, осколків фотоподілу, пошкоджень від нейтронів. Установлено, що найбільшій внесок у швидкість утворення зміщень в урановій мішені створюють осколки фотоподілу. Проведен расчет скорости образования смещений в урановой мишени источника нейтронов ННЦ ХФТИ под действием облучения высокоэнергетическими электронами с энергией 100 МэВ. Рассмотрены вклады упругих и неупругих процессов: рассеяния высокоэнергетических электронов и гамма-квантов, рождения фотонейтронов, осколков фотоделения, повреждений от нейтронов. Установлено, что наибольший вклад в скорость образования повреждений в урановой мишени вносят осколки фотоделения.